Batman. Soul of the dragon [videorecording (Blu-Ray)] (Warner Bros. Home Entertainment, 2021)
Set in the midst of the swinging 1970s, this Elseworlds adventure finds Bruce Wayne training under a master sensei. It is here that Bruce, along with other elite students, is forged in the fire of the martial arts discipline. The lifelong bonds they form will be put to the test when a deadly menace arises from their past. It will take the combined efforts of Batman and world-renowned martial artists Richard Dragon, Ben Turner, and Lady Shiva to battle the monsters of this world and beyond!